Teaching about harmful alcohol use in undergraduate nursing: implications for professional practice - Maciel, Marjorie Ester Dias; Vargas, Divane de (Revista de Graduação USP, 2017)
This is a paper of reflection whose goal is to make some considerations about how it has been teaching about harmful alcohol use in undergraduate courses in nursing. It appears that the teaching of this subject is related to the disciplines of mental health and psychiatric nursing and few hours of these disciplines have devoted to this theme, which is insufficient to train future nurses to be able to act against this problem. Thus, it suggests changes in the way teaching and reformulation of the nursing curriculum for this subject is best contemplated.